Performance evaluation of UWB-BAN with friis's formula and CLEAN algorithm - Koonchiang, Krisada; Arpasilp, Dissakan; Promwong, Sathaporn (My University, 2013)
An ultra wideband impulse radio (UWB-IR) are developing to use in communication system and medical application because it has been an increase interest in using on body for health monitoring and body area networks (BAN). This research want to improving UWB channel propagation on body by using CLEAN algorithm for eliminate noise in channel propagation. In addition to, we use result from previous work for easier to compare performance before system. Moreover, in this paper us analysis performance of system when using CLEAN algorithm and compare without use CLEAN Algorithm by us will show BER in each position on body for analysis performance of CLEAN algorithm can be reduce noise or effect on body when without CLEAN Algorithm. © 2013 Springer Science+Business Media Dordrecht(Outside the USA).
Keywords: BAN; CLEAN Algorithm; Friis's transmission formula; Impulse radio; UWB